GENOTYPING AND DNA SEQUENCING DIVERGENCE OF TOXOPLASMA GONDII STRAINS ASSOCIATED WITH RABBIT TOXOPLASMOSIS, IRAQ: Pharmaceutical Science-Clinical Laboratories Science - MUHANNAD SHWEASH; NOOR N AL-HAYANI; HATEM M. HADEED; THULFIQAR FAWWAZ MUTAR (International Journal of Life Science and Pharma Research, 2022)
The aim of this study is to determine the genetic patterns and sequencing of Toxoplasma gondii (T. gondii) isolated from humans and inoculated into rabbits to determine the effect of these strains on animals and the changes that occur in these strains. Therefore, DNA sequencing is necessary to apply with genetic developing for microorganisms to determine the relation between different organisms and how they are developed. Thirty-eight samples of congenital Toxoplasmosis were collected from the placenta of women who have had abortion and after their development were inoculated into rabbits. Seventeen samples of whole blood from rabbits were investigated. Iraqi human T. gondii were infected in 38 samples of rabbits, 17 samples out of 38 underwent gene sequence work from period 15th September 2015 to 10th may 2016. Data from 38 samples using the Surface Antigen Glycoproteins (SAG2) gene locus according to geno typing indicated that 22 out of 38 was types II, while 8 samples were types I and 8 showed types III. The results showed that there was a significant effect by the congenital Toxoplasmosis, which was developed in the bodies of rabbits, different strains of I, II, III, taken from the placenta of women who have had abortion because they were infected with T. gondii.